2017
DOI: 10.5433/1679-0359.2017v38n4p2001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shed rooftype and babassu pie on the productive characteristics of meat quails

Abstract: We aimed to evaluate the effects of shed roof(SR) typeand the inclusion of babassu pie (BP) in rations on the productive characteristics ofmeat quailsfrom days 14 to 28 and days14 to 40. We studied 896 meatquails. The experimental design was completely randomized with a 4x4 factorial arrangement, using four types of shedroofs (fiber cement, ceramic, straw, and painted fiber cement) and four rations (with 0, 5, 10, and 15% inclusion of babassu pie). The performance variables evaluated from 14 to 28 and 14 to 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Nevertheless, this type of roof has an advantage over the others in terms of thermal control. Borges et al [20] tested four types of roofs for quail sheds and found that ceramic roofing provided the best thermal comfort. A ridge vent is an opening in the roof that allows hot air to escape from the shed [15] and is indicated for warm regions.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this type of roof has an advantage over the others in terms of thermal control. Borges et al [20] tested four types of roofs for quail sheds and found that ceramic roofing provided the best thermal comfort. A ridge vent is an opening in the roof that allows hot air to escape from the shed [15] and is indicated for warm regions.…”
Section: Discussionmentioning
confidence: 99%